PENGARUH LAMA PENYIMPANAN TERHADAP DAYA BERKECAMBAH BENIH RAMBUTAN (Nephelium lappaceum) - Dyah Erlina Sulistyaningrum; Tri Rahayuningsih; Rijono Eko Muharijanto; Edy Prayitno (Institute of Computer Science (IOCS), 2023)
Rambutan seeds are classified as non-digestible seeds that require special storage techniques. Non-resistant seeds cannot be stored for a long time due to their high moisture content. The purpose of rambutan seed storage is the production of seed material or the preservation of plant material. The aim of this study was to determine the power off germination and germination time of seed-stored rambutan. His research is descriptive and his findings are tabulated and explained. Administered seed treatments were storage or no direct sowing treatment, seed storage at 16°C for 3 days, and seed storage at 16°C for 6 days. Open containers were used to store litchi seeds. Rambutan seeds stored for 3 days at 16°C had a germination rate of 75%, the same as rambutan seed treatments without seed storage or directly sown lychee seeds. It was found that the germination time of rambutan seeds treated at 16 °C for 6 days was delayed by 4 days compared to rambutan seeds treated at 16 °C for 3 days, otherwise the germination time was delayed. rice field. kept. The results showed that rambutan seeds could be stored in an open container at 16°C for 3 days.